Computer-Aided Detection of Retinopathy of Prematurity Severity in Preterm Infants via Measurement of Temporal Vessel Width and Angle - Yo-Ping Huang; Yo-Ping Huang; Yo-Ping Huang; Spandana Vadloori; Eugene Yu-Chuan Kang; Eugene Yu-Chuan Kang; Wei-Chi Wu; Wei-Chi Wu (Frontiers Media S.A., 2022)
Retinopathy of prematurity (ROP) is a retinal disorder that occurs in preterm infants with low birth weight and is the leading cause of preventable blindness in children. Early identification of high-risk patients and early diagnosis and timely treatment of ROP can substantially improve patients' visual outcomes. However, manual screening consumes both time and resources. Telescreening using retinal fundus images has the potential to reduce the burden engendered by the necessity of on-site screening. Recently, substantial progress has been made in using computer-aided diagnosis with retinal fundus images, and this approach has attracted considerable attention for the diagnosis of eye diseases. Abnormalities of and alterations in retinal blood vessels may relate to the occurrence and progression of ROP. In this study, we examined the hypothesis that ROP severity may be associated with the angle and width of arteries and veins. We computationally determined the artery-artery and vein-vein angles in the temporal quadrants-the temporal artery angle (TAA) and temporal vein angle (TVA)-under normal conditions and in different ROP stages. We also estimated retinal vessel width-temporal artery width (TAW) and temporal vein width (TVW)-by applying the Radon transform method to fundus images. Our results revealed significant decreases in TAA and TVA and increases in TAW and TVW with increasing ROP severity (all P < 0.0001).In addition, we observed positive TAA-TVA and TAW-TVW correlations (both P < 0.0001). The TAA was negatively correlated with the TAW (r = −0.162, P = 0.0314). These retinal vessel features may be useful in assisting ophthalmologists in the early detection of ROP and its progression.